Evation of High-Mobility Group Box 1 after Clinical Autologous Islet Transplantation and Its Inverse Correlation with Outcomes. Issue 2 (March 2014) - Itoh, Takeshi; Iwahashi, Shuichi; Kanak, Mazhar A.; Shimoda, Masayuki; Takita, Morihito; Chujo, Daisuke; Tamura, Yoshiko; Rahman, Ana M.; Chung, Wen Y.; Onaca, Nicholas; Coates, P. Toby H.; Dennison, Ashley R.; et al.
A major problem after clinical autologous islet transplantation (AIT) is the difficulty in achieving insulin independence. To follow up on our demonstration in a murine model that high-mobility group box 1 (HMGB1) was released from islets and involved in early loss of transplanted islets, we tested the role of HMGB1 in clinical AIT. Serum HMGB1 levels from 15 AIT patients were significantly elevated during islet infusion (7.6 ± 1.2 ng/ml) and 24 h after infusion (8.0 ± 1.4 ng/ml) compared to admission levels (2.4 ± 0.6 ng/ml). The first elevation of HMGB1 was associated with islet damage, but the later elevation was not. The change in the HMGB1 level from admission to first peak (ΔHMGB1) was significantly higher in the AIT group (8.1 ± 1.1 ng/ml) than in the pancreatectomy-only control (2.2 ± 0.5 ng/ml) ( p < 0.05). Circulating serum levels of soluble receptor for advanced glycation end products (sRAGE) were also elevated during islet infusion. In vitro studies demonstrated that damaged human islets released HMGB1 but not sRAGE. In terms of outcomes, the insulin-free group showed significantly lower ΔHMGB1 (5.2 ± 0.6 ng/ml) and higher ΔsRAGE (2.3 ± 0.6 ng/ml) than the insulin-dependent group (10.6 ± 1.9 ng/ml and 0.7 ± 0.2 ng/ml, respectively). The ΔHMGB1 correlated with the number of white blood cell, IP-10, EGF, and eotaxin. In conclusion, serum HMGB1 was elevated in AIT and could be associated with inflammatory reactions that deteriorate islet engraftment. Therefore, anti-HMGB1 therapy might be a candidate for further improving the outcomes of clinical AIT.